2019
DOI: 10.1111/jpy.12913
|View full text |Cite
|
Sign up to set email alerts
|

The macromolecular composition of noncalcified marine macroalgae

Abstract: The macromolecular composition of macroalgae influences nutrient flow and food quality in aquatic ecosystems and the value of macroalgae species for human consumption, aquaculture, biofuels, and other applications. We used literature data (125 publications, 1,117 observations) and a hierarchal Bayesian statistical model to estimate the average macromolecular composition, protein, lipid, and carbohydrate of macroalgae as a whole and at the phylum level. Our focus was on marine, noncalcified macroalgae sampled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Seaweeds of the phylum Ochrophyta had higher C:N than the C:N for either Rhodophyta or Chlorophyta, which is consistent with observations made in previous studies (Fiset et al, 2019; Niell, 1976). Phylogenetic differences in pigment type and content, along with amount of structural material could help explain this trend in C:N. All seaweeds have chlorophyll a , but the accessory pigments of seaweeds differ among the three major phyla (Hurd et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Seaweeds of the phylum Ochrophyta had higher C:N than the C:N for either Rhodophyta or Chlorophyta, which is consistent with observations made in previous studies (Fiset et al, 2019; Niell, 1976). Phylogenetic differences in pigment type and content, along with amount of structural material could help explain this trend in C:N. All seaweeds have chlorophyll a , but the accessory pigments of seaweeds differ among the three major phyla (Hurd et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the higher contents of nitrogen in the pigments of Rhodophyta and Chlorophyta seaweeds may explain their higher tissue %N and corresponding average lower C:N ratios compared with Ochrophyta seaweeds. Also, the largest species of seaweed belong to the Ochrophyta (Scott, 2017), and therefore, they may need additional structural support in the form of carbon-rich cell wall polysaccharides and alginates to prevent wavedamage and breakage (Atkinson & Smith, 1983;Fiset et al, 2019). This likely contributes to the higher C:N ratio in Ochrophyta compared with other phyla.…”
Section: Taxonomic Influences On Seaweed C:nmentioning
confidence: 99%
“…For instance, they include ulvan, a sulfated glucuronoxylorhamnan, in green macroalgae Ulva lactuca [5]; alginate and sulfated polysaccharides, such as fucoidan, in brown macroalgae, such as Saccharina latissima, Laminaria digitata, and Fucus vesiculosus [4,6,7]. Macromolecular composition of seaweed is also varied with seasons and nutrient availability [8,9]. For instance, it has been shown that the highest carbohydrate content was in spring [10] and summer [11] in green seaweed, U. lactuca, with increased rhamnosyl and glucuronoyl residues in April [10].…”
Section: Introductionmentioning
confidence: 99%
“…This might also explain the lower values found here compared with Angell et al (2017). Even when comparing literature with the same species, differences within species can have an effect on the results.The composition of the four species tested did not always correspond to the median macromolecular content of 1117 observations from seaweeds found in the wild (Fiset et al 2019). The U. lactuca in this study with 9.1 g protein (100 g) −1 DW had a relatively low protein content compared with the median value for Chlorophyceae by Fiset et al (2019) with roughly 11.0 g protein (100 g) −1 DW, and the protein content of C. crispus and A. nodosum found in this study was high, compared with the median protein content of Rhodophyceae and Phaeophyceae with roughly 11.0 and 8.0 g protein (100 g) −1 DW, respectively.…”
Section: Discussionmentioning
confidence: 73%